Hard alloy and cutting tool using same
By using cemented carbide containing high-content tungsten carbide particles and cobalt-bound phases, and controlling vanadium and chromium distribution in its interface area, the problem of short life of existing cutting tools is solved, and longer tool life and better tool life are achieved wear resistance.
Patent Information
- Application Number
- CN202380047908.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-02-21
AI Technical Summary
During the processing of semiconductor packaging substrates, the life of existing cutting tools is shorter, making it difficult to meet the needs of reduced costs and extended tool service life.
A new type of cemented carbide is adopted, which contains 80% by volume % and 0.1% by volume % by volume % by binding phase, and the bonding phase contains 50% by mass of cobalt, and is in the interface area between the tungsten carbide particles and the bonding phase. There are specific vanadium and chromium distributions.
When used as a cutting tool, the cemented carbide significantly improves the wear resistance and breakage resistance of the tool and extends the service life of the tool, especially during the processing of semiconductor packaging substrates.
Smart Images

Figure CN119497760A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to cemented carbide and a cutting tool using the same. Background Art
[0002] Conventionally, cemented carbide having tungsten carbide (WC) particles and a binder phase containing cobalt or the like as a main component has been used as a material for cutting tools (Patent Documents 1 and 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-098393
[0006] Patent Document 2: Japanese Patent Application Publication No. 2021-110010 Summary of the invention
[0007] The cemented carbide disclosed in the present invention is a cemented carbide having a plurality of tungsten carbide particles and a bonding phase, wherein:
[0008] The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total,
[0009] The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase,
[0010] The cemented carbide contains 0.03 atomic % or more and 0.90 atomic % or less of vanadium,
[0011] The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium,
[0012] The binding phase contains 50 mass % or more of cobalt,
[0013] The results of line analysis along a first direction from a position X1 disposed in the tungsten carbide particle toward a position X2 disposed in the binding phase adjacent to the tungsten carbide particle using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first region of a first graph obtained in a coordinate system in which the X-axis is the distance from the position X1 and the Y-axis is the intensity.
[0014] Maximum Strength of Tungsten I W The distance P W , represents the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 、The maximum strength of vanadium I V The distance P V 、The maximum strength of chromium ICr The distance P Cr , represents the maximum strength of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 and the maximum intensity I Co The distance P Co Show P W <P W70 <P V <P Cr <P Co70 <P Co relationship,
[0015] The first region is a region between a distance P1 and a distance P2 in the first curve graph, wherein the distance P1 is a distance from the distance P2 on the X-axis. V The distance from the origin of the coordinate system to the coordinate system is 3 nm, and the distance P2 is 3 nm from the P V The distance to the side opposite to the origin is 3 nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic cross-sectional view of the cemented carbide according to the first embodiment.
[0017] Figure 2 An example of a first graph showing cemented carbide according to the first embodiment.
[0018] Figure 3 This is a high-angle annular dark field (HAADF: high-angle annular darkfield) image of a cross section of cemented carbide.
[0019] Figure 4 This is a diagram for explaining a method for confirming that vanadium atoms and chromium atoms exist at the C site of tungsten carbide.
[0020] Figure 5 This is a schematic diagram of a cutting tool according to the second embodiment. DETAILED DESCRIPTION
[0021] [Problems to be Solved by the Present Disclosure]
[0022] With the expansion of 5G (fifth generation mobile communication system), the demand for semiconductor package substrates has increased. Small diameter drills are used to perform hole processing on semiconductor package substrates. From the perspective of cost reduction, cutting tools with longer life are also required when used for processing semiconductor package substrates.
[0023] Therefore, an object of the present disclosure is to provide a cemented carbide that can provide a cutting tool having a long tool life when used as a material for a cutting tool, particularly in processing a semiconductor package substrate, and a cutting tool including the cemented carbide.
[0024] [Effects of the present disclosure]
[0025] According to the present disclosure, it is possible to provide a cemented carbide that can provide a cutting tool having a long tool life when used as a material for a cutting tool, particularly in processing a semiconductor package substrate, and a cutting tool including the cemented carbide.
[0026] [Description of Embodiments of the Present Disclosure]
[0027] First, embodiments of the present disclosure will be described by way of examples.
[0028] (1) The cemented carbide disclosed in the present invention is a cemented carbide having a plurality of tungsten carbide particles and a binder phase, wherein:
[0029] The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total,
[0030] The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase,
[0031] The cemented carbide contains 0.03 atomic % or more and 0.90 atomic % or less of vanadium,
[0032] The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium,
[0033] The binding phase contains 50 mass % or more of cobalt,
[0034] The results of line analysis along a first direction from a position X1 disposed in the tungsten carbide particle toward a position X2 disposed in the binding phase adjacent to the tungsten carbide particle using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first region of a first graph obtained in a coordinate system in which the X-axis is the distance from the position X1 and the Y-axis is the intensity.
[0035] Maximum Strength of Tungsten I W The distance P W , represents the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 、The maximum strength of vanadium I V The distance P V 、The maximum strength of chromium I Cr The distance PCr , represents the maximum strength of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 and the maximum intensity I Co The distance P Co Show P W <P W70 <P V <P Cr <P Co70 <P Co relationship,
[0036] The first region is a region between a distance P1 and a distance P2 in the first curve graph, wherein the distance P1 is a distance from the distance P2 on the X-axis. V The distance from the origin of the coordinate system to the coordinate system is 3 nm, and the distance P2 is 3 nm from the P V The distance to the side opposite to the origin is 3 nm.
[0037] According to the present disclosure, it is possible to provide a cemented carbide that can provide a cutting tool having a long tool life when used as a material for a cutting tool, particularly in processing a semiconductor package substrate, and a cutting tool including the cemented carbide.
[0038] (2) It can also be that, based on the above (1), the V The vanadium atoms and the Cr The chromium atoms are present at the W site of tungsten carbide.
[0039] (3) In addition to the above (1) or (2), the cemented carbide may contain 18 volume % or less of the binder phase. This further improves tool life.
[0040] (4) The cutting tool of the present disclosure is a cutting tool including a cutting edge made of the cemented carbide according to any one of (1) to (3) above.
[0041] The cutting tool of the present disclosure can also have a long tool life, particularly when used for processing a semiconductor package substrate.
[0042] [Details of the embodiments of the present disclosure]
[0043] Hereinafter, specific examples of the cemented carbide and cutting tool disclosed in the present invention will be described with reference to the accompanying drawings. In the accompanying drawings disclosed in the present invention, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the accompanying drawings, and may not necessarily represent the actual dimensional relationships.
[0044] In the present disclosure, expressions in the format of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only a unit is recorded in B, the unit of A is the same as that of B.
[0045] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the atomic ratio within the stoichiometric range.
[0046] In the present disclosure, when more than one numerical value is recorded as the lower limit and the upper limit of the numerical range, a combination of any numerical value recorded in the lower limit and any numerical value recorded in the upper limit is also disclosed. For example, when more than a1, more than b1, and more than c1 are recorded as the lower limit, and less than a2, less than b2, and less than c2 are recorded as the upper limit, more than a1 and less than a2, more than a1 and less than b2, more than a1 and less than c2, more than b1 and less than a2, more than b1 and less than b2, more than b1 and less than c2, more than c1 and less than a2, more than c1 and less than b2, more than c1 and less than c2 are disclosed.
[0047] [Embodiment 1: Cemented Carbide]
[0048] A cemented carbide according to one embodiment of the present disclosure (hereinafter also referred to as “embodiment 1”) is a cemented carbide having a plurality of tungsten carbide particles and a binder phase, wherein:
[0049] The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total,
[0050] The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase,
[0051] The cemented carbide contains 0.03 atomic % or more and 0.90 atomic % or less of vanadium,
[0052] The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium,
[0053] The binding phase contains 50 mass % or more of cobalt,
[0054] The results of line analysis along a first direction from a position X1 disposed in the tungsten carbide particle toward a position X2 disposed in the binding phase adjacent to the tungsten carbide particle using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first region of a first graph obtained in a coordinate system in which the X-axis is the distance from the position X1 and the Y-axis is the intensity.
[0055] Maximum Strength of Tungsten IW The distance P W , represents the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 、The maximum strength of vanadium I V The distance P V 、The maximum strength of chromium I Cr The distance P Cr , represents the maximum strength of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 and the maximum intensity I Co The distance P Co Show P W <P W70 <P V <P Cr <P Co70 <P Co relationship,
[0056] The first region is a region between a distance P1 and a distance P2 in the first curve graph, wherein the distance P1 is a distance from the distance P2 on the X-axis. V The distance from the origin of the coordinate system to the coordinate system is 3 nm, and the distance P2 is 3 nm from the P V The distance to the side opposite to the origin is 3 nm.
[0057] When the cemented carbide of the first embodiment is used as a material for a cutting tool, in particular, in processing a semiconductor package substrate, a cutting tool having a long tool life can be provided. The reason for this is not clear, but is presumed as follows.
[0058] The cemented carbide of embodiment 1 has a plurality of tungsten carbide particles (hereinafter, also referred to as "WC particles") and a binding phase, and the total content of the WC particles and the binding phase of the cemented carbide is more than 80 volume %. Thus, the cemented carbide has high hardness and high strength, and a cutting tool using the cemented carbide can have excellent wear resistance and breakage resistance.
[0059] The cemented carbide of Embodiment 1 contains a binder phase of 0.1 volume % or more and 20 volume % or less, and the binder phase contains 50 mass % or more of cobalt. Thus, the cemented carbide has high hardness and high strength, and a cutting tool using the cemented carbide can have excellent wear resistance and breakage resistance.
[0060] The cemented carbide of the first embodiment contains 0.03 atomic % or more and 0.90 atomic % or less of vanadium and 0.01 atomic % or more and 1.20 atomic % or less of chromium. Vanadium and chromium have the effect of inhibiting the grain growth of tungsten carbide particles. W <P W70 <P V <P Cr <P Co70 <P Co Thus, the effect of suppressing the grain growth of tungsten carbide particles is further improved. Therefore, in the cemented carbide of embodiment 1, the formation of abnormal structure accompanying the generation of coarse particles is suppressed, and the cutting tool using the cemented carbide can have excellent breakage resistance.
[0061] <Composition of cemented carbide>
[0062] like Figure 1 As shown, the cemented carbide 3 of embodiment 1 has a plurality of tungsten carbide particles 1 (hereinafter, also referred to as "WC particles") and a binding phase 2, and the total content of the WC particles and the binding phase of the cemented carbide 3 is 80 volume % or more. The lower limit of the total content of the WC particles and the binding phase of the cemented carbide can be 82 volume % or more, 84 volume % or more, 85 volume % or more, or 86 volume % or more. The upper limit of the total content of the WC particles and the binding phase of the cemented carbide can be 100 volume % or less. From the viewpoint of manufacturing, the upper limit of the total content of the WC particles and the binding phase of the cemented carbide can be 99 volume % or less, or 98 volume % or less. The total content of the WC particles and the binding phase of the cemented carbide can be 80 volume % or more and 100 volume % or less, 82 volume % or more and 100 volume % or less, or 84 volume % or more and 100 volume % or less.
[0063] The cemented carbide of the first embodiment may be composed of a plurality of tungsten carbide particles and a binder phase. The cemented carbide of the present embodiment may further include other phases in addition to the tungsten carbide particles and the binder phase. Examples of the composition of the other phases include TiCN and TaC.
[0064] The cemented carbide of embodiment 1 can be made of tungsten carbide particles, bonding phase and other phases. Allow the content of other phases of cemented carbide within the scope of not damaging the effect of the present disclosure. For example, the content of other phases of cemented carbide can be more than 0 volume % and less than 20 volume %, can also be more than 0 volume % and less than 18 volume %, can also be more than 0 volume % and less than 16 volume %. In this case, the total content of the WC particles of cemented carbide and bonding phase can be more than 80 volume % and less than 100 volume %, can also be more than 82 volume % and less than 100 volume %, can also be more than 84 volume % and less than 100 volume %.
[0065] The cemented carbide of embodiment 1 may contain impurities. As the impurities, for example, calcium (Ca) and sulfur (S) can be listed. The content of impurities in the cemented carbide is allowed within the range that does not damage the effect of the present disclosure. For example, the content of impurities in the cemented carbide is preferably 0 mass % or more and less than 0.1 mass %. The content of impurities in the cemented carbide is measured by ICP emission analysis (Inductively Coupled Plasma Emission Spectroscopy (measurement device: Shimadzu Corporation "ICPS-8100" (trademark)).
[0066] The lower limit of the containing rate of the tungsten carbide particles of the cemented carbide of embodiment 1 can be more than 60 volume %, can also be more than 62 volume %, can also be more than 64 volume %, can also be more than 68 volume %.The upper limit of the containing rate of the tungsten carbide particles of this cemented carbide can be below 99.9 volume %, can also be below 99.2 volume %, can also be below 99 volume %, can also be below 98 volume %, can also be below 96 volume %, can also be below 94 volume %.The containing rate of the tungsten carbide particles of this cemented carbide can be more than 60 volume % and below 99.9 volume %, can also be more than 60 volume % and below 99.2 volume %, can also be more than 64 volume % and below 96 volume %, can also be more than 68 volume % and below 94 volume %.
[0067] The cemented carbide of embodiment 1 comprises a bonding phase of more than 0.1 volume % and less than 20 volume %. From the viewpoint of improving toughness, the lower limit of the containing rate of the bonding phase of this cemented carbide is more than 0.1 volume %, can also be more than 1 volume %, can also be more than 2 volume %, can also be more than 3 volume %, can also be more than 4 volume %, can also be more than 8 volume %. From the viewpoint of improving hardness, the upper limit of the containing rate of the bonding phase of this cemented carbide is less than 20 volume %, can also be less than 19 volume %, can also be less than 18 volume %, can also be less than 17 volume %, can also be less than 16 volume %, can also be less than 15 volume %. The containing rate of the bonding phase of this cemented carbide can be more than 0.1 volume % and less than 18 volume %, can also be more than 1 volume % and less than 18 volume %, can also be more than 3 volume % and less than 17 volume %, can also be more than 4 volume % and less than 16 volume %, can also be more than 8 volume % and less than 15 volume %. When the content of the binder phase of cemented carbide is 18% by volume or less, the hardness of the cemented carbide is further improved, and the wear resistance is further improved, so that the tool life of the cutting tool using the cemented carbide as a material is further improved.
[0068] The content rate (volume %) of tungsten carbide particles in cemented carbide and the content rate (volume %) of the binder phase in cemented carbide are measured as follows.
[0069] (A1) An arbitrary position of cemented carbide is cut out to expose a cross section, and the cross section is mirror-finished using a cross-section polisher (manufactured by Nippon Denshi Co., Ltd.).
[0070] (B1) The mirror-finished surface of the cemented carbide was analyzed using a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) (apparatus: Gemini 450 (trademark) manufactured by Carl Zeiss) to identify the elements contained in the cemented carbide.
[0071] (C1) The mirror-finished surface of cemented carbide was photographed using a scanning electron microscope (SEM) to obtain a reflected electron image. The photographing area of the photographed image was set at the central part of the cross section of the cemented carbide, i.e., the position of the part where the properties are obviously different from the main part, such as the vicinity of the surface of the cemented carbide, which does not include the cemented carbide (the position where the photographing area is the main part of the cemented carbide). The observation magnification was 5000 times. The measurement conditions were an acceleration voltage of 3 kV, a current value of 2 nA, and a working distance (WD) of 5 mm.
[0072] (D1) The imaging region of (C1) is analyzed using an energy dispersive X-ray analyzer (SEM-EDX) attached to the SEM to determine the distribution of the elements determined in (B1) in the imaging region and obtain an element mapping image.
[0073] (E1) The reflected electron image obtained in the above (C1) is taken into a computer and binarized using image analysis software (OpenCV, SciPy). In the binarized image, the tungsten carbide particles are represented by white, and the binding phase is represented by gray to black. In addition, the threshold of binarization varies according to the contrast, so it is set for each image.
[0074] (F1) By overlapping the elemental mapping image obtained in (D1) above with the binarized image obtained in (E1) above, the existence areas of tungsten carbide particles and the binding phase are determined on the binarized image. Specifically, the area where tungsten (W) and carbon (C) exist in the elemental mapping image, which is represented by white in the binarized image, corresponds to the existence area of tungsten carbide particles. The area where cobalt (Co) exists in the elemental mapping image, which is represented by gray to black in the binarized image, corresponds to the existence area of the binding phase.
[0075] (G1) A rectangular measurement field of 24.9 μm×18.8 μm is set in the binarized image, and the area percentages of the tungsten carbide particles and the binder phase are measured using the image analysis software, with the area of the entire measurement field as the denominator.
[0076] (H1) The measurement of (G1) is performed in five different non-overlapping measurement fields. In this specification, the average of the area percentage of tungsten carbide particles in the five measurement fields is equivalent to the content (volume %) of tungsten carbide particles in the cemented carbide, and the average of the area percentage of the binding phase in the five measurement fields is equivalent to the content (volume %) of the binding phase in the cemented carbide.
[0077] In the case where the cemented carbide contains other phases in addition to WC particles and a binding phase, the content of the other phases of the cemented carbide can be obtained by subtracting the content (volume %) of the tungsten carbide particles and the content (volume %) of the binding phase measured according to the above steps from the entire cemented carbide (100 volume %).
[0078] The following situation was confirmed: as long as it is within the scope of the applicant's measurement and as long as the measurement is performed on the same sample, even if the cut-out part of the cemented carbide section, the shooting area described in (C1) above, and the measurement field of view described in (G1) above are arbitrarily set, the content of tungsten carbide particles and the content of the binding phase in the cemented carbide are measured multiple times according to the above steps, and the deviation of the measurement results is very small. Even if the cut-out part of the cemented carbide section, the shooting area, and the measurement field of view are arbitrarily set, the results will not change arbitrarily.
[0079] <Tungsten Carbide Particles>
[0080] In the first embodiment, the tungsten carbide particles include at least one of "pure WC particles (WC containing no impurity elements at all, including WC with an impurity element content less than the detection limit)" and "WC particles containing impurity elements intentionally or inevitably within a range that does not impair the effects of the present disclosure". The content of impurities in the tungsten carbide particles (when there are two or more elements constituting the impurities, the total concentration of the elements) is less than 0.1% by mass. The content of impurity elements in the tungsten carbide particles is measured by ICP emission analysis.
[0081] In Embodiment 1, the average particle size of the tungsten carbide particles is not particularly limited. The average particle size of the tungsten carbide particles can be, for example, 0.1 μm to 3.5 μm. It was confirmed that the cemented carbide of Embodiment 1 can have a long tool life regardless of the average particle size of the tungsten carbide particles.
[0082] <Combination Phase>
[0083] In embodiment 1, the bonding phase includes more than 50% by mass of cobalt. Thus, it is possible to impart excellent toughness to the cemented carbide. The lower limit of the cobalt content of the bonding phase can be more than 52% by mass, can be more than 57% by mass, can be more than 60% by mass, can be more than 63% by mass. The upper limit of the cobalt content of the bonding phase can be less than 100% by mass, can be less than 100% by mass, can be less than 99% by mass, can be less than 98% by mass, can be less than 95% by mass, can be less than 90% by mass. The cobalt content of the bonding phase can be more than 50% by mass and less than 100% by mass, can be more than 60% by mass and less than 99% by mass, can be more than 63% by mass and less than 98% by mass.
[0084] The method for determining the cobalt content of the binder phase is as follows. The region where the binder phase exists is determined on the image after binarization by the same method as (A1) to (F1) of the method for determining the content of tungsten carbide particles, the content of the binder phase, and the content of hard phase particles in the above-mentioned cemented carbide. The region where the binder phase exists is analyzed using SEM-EDX to determine the cobalt content of the binder phase.
[0085] The following situation was confirmed: as long as it is within the scope of the applicant's measurement and as long as the measurement is performed on the same sample, even if the cut-out part of the cross-section of the cemented carbide and the shooting area described in (C1) above are arbitrarily set, the cobalt content of the binding phase is measured multiple times according to the above steps, and the deviation of the measurement results is very small. Even if the cut-out part of the cross-section of the cemented carbide and the shooting area are arbitrarily set, the results will not change arbitrarily.
[0086] In the first embodiment, the binding phase may further include at least one first element selected from the group consisting of boron (B), aluminum (Al), silicon (Si), iron (Fe), nickel (Ni), germanium (Ge), ruthenium (Ru), rhenium (Re), osmium (Os), iridium (Ir), and platinum (Pt) in addition to cobalt. The binding phase may be composed of cobalt, the first element, and inevitable impurities. Examples of the inevitable impurities include manganese (Mn), magnesium (Mg), calcium (Ca), sulfur (S), and the like.
[0087] <Vanadium>
[0088] The cemented carbide of embodiment 1 contains vanadium of 0.03 atomic % or more and 0.90 atomic % or less. From the viewpoint of improving the grain growth inhibition effect, the lower limit of the vanadium content of the cemented carbide is 0.03 atomic % or more, and may be 0.10 atomic % or more, and may be 0.20 atomic % or more, and may be 0.30 atomic % or more. From the viewpoint of suppressing the precipitation of coarse (W, V) C phase, the upper limit of the vanadium content of the cemented carbide is 0.90 atomic % or less, and may be 0.80 atomic % or less, and may be 0.70 atomic % or less. The vanadium content of the cemented carbide may be 0.10 atomic % or more and 0.90 atomic % or less, and may be 0.20 atomic % or more and 0.80 atomic % or less, and may be 0.30 atomic % or more and 0.70 atomic % or less.
[0089] The vanadium content of the cemented carbide was measured by ICP emission analysis.
[0090] <Chrome>
[0091] The cemented carbide of embodiment 1 contains chromium of 0.01 atomic % or more and 1.20 atomic % or less. From the viewpoint of improving the grain growth inhibition effect, the lower limit of the chromium content of the cemented carbide is 0.01 atomic % or more, and may be 0.10 atomic % or more, or 0.20 atomic % or more. From the viewpoint of suppressing the precipitation of coarse (W, Cr) C phase, the upper limit of the chromium content of the cemented carbide is 1.20 atomic % or less, and may be 0.80 atomic % or less, or 0.70 atomic % or less. The chromium content of the cemented carbide may be 0.10 atomic % or more and 0.80 atomic % or less, and may be 0.20 atomic % or more and 0.70 atomic % or less.
[0092] The chromium content of the cemented carbide was measured by ICP emission analysis.
[0093] <Line Analysis>
[0094] use Figure 2, the results of line analysis along a first direction from a position X1 disposed in a tungsten carbide particle toward a position X2 disposed in a binding phase adjacent to the tungsten carbide particle in the cemented carbide of embodiment 1 using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are described. Figure 2 This is an example of a first graph. For the cemented carbide of Embodiment 1, a line analysis is performed on the elements contained in the cemented carbide, namely, tungsten, cobalt, vanadium, and cobalt, and the obtained results are shown in a coordinate system where the X-axis is the distance from the position X1 and the Y-axis is the intensity, thereby obtaining a first graph. Figure 2 In the cemented carbide shown, the binder phase is cobalt.
[0095] like Figure 2 As shown, in the first region of the first graph, the maximum intensity I of tungsten W The distance P W , represents the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 、The maximum strength of vanadium I V The distance P V 、The maximum strength of chromium I Cr The distance P Cr , represents the maximum strength of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 , Maximum Strength I Co The distance P Co Show P W <P W70 <P V <P Cr <P Co70 <P Co Here, the first region is the region from distance P1 to distance P2 in the first curve graph, where distance P1 is from P2 on the X-axis. V The distance to the origin of the coordinate system is 3nm, and the distance P2 is from P V The distance to the side opposite to the origin is 3 nm. W70 It means that there are multiple representations of intensity I in the first curve graph. W70 In the case of distances of, the maximum distance among these distances is distance P W70 .exist Figure 2 In the first graph, the intensity I W70 There are four distances. The smallest distance P Co70 It means that there are multiple representations of intensity I in the first curve graph. Co70 In the case of distances, the minimum distance among these distances is distance P Co70 .exist Figure 2 In the first graph, the intensity I Co70 There is a distance of .
[0096] P W <P W70 <P V <P Cr <P Co70 <P Co In the relationship between W <P V <P Cr <P Co The relationship indicates that in the first region including the interface between WC particles and the binder phase, the V The maximum concentration region of vanadium exists at a distance P Cr The maximum concentration region of chromium is closer to the position of the WC particles, and the maximum concentration region of chromium exists at a position closer to the binding phase than the maximum concentration region of vanadium.
[0097] P W70 <P V The relationship indicates that the distance P V The maximum vanadium concentration area is located outside the WC particles, not inside the WC particles. Cr <P Co70 The relationship between P and Cr indicates that the maximum chromium concentration region is located outside the binding phase, not inside the binding phase. W70 <P V <P Cr <P Co70 The relationship of indicates that the maximum concentration region of vanadium and the maximum concentration region of chromium exist in the interface region between the WC particles and the binder phase.
[0098] In the present disclosure, the acquisition of the first curve graph based on the line analysis of cemented carbide and the analysis results is carried out according to the following steps. Using an argon ion slicer ("Low Temperature Ion Slicer IB-09060BCIS" (trademark) manufactured by JEOL Ltd.), the cemented carbide is sliced into a thickness of 30 to 100 nm under the conditions of an acceleration voltage of 6 kV and a finishing of 2 kV to prepare a measurement sample. Next, using a TEM (Transmission Electron Microscopy) ("JEM-ARM300F2" (trademark) manufactured by JEOL Ltd.), the measurement sample is observed at 200,000 times under the conditions of an acceleration voltage of 200 V, thereby obtaining a first image (not shown).
[0099] In the first image, the tungsten carbide particles are observed as white areas, and the binder phase is observed as black areas. In the first image, the interface between the tungsten carbide particles and the binder phase is arbitrarily selected.
[0100] Next, the selected interface is positioned so that it passes near the center of the image, and the observation magnification is adjusted so that the field size becomes 5nm×5nm, thereby obtaining a second image (not shown). In the second image, the elongation direction of the interface elongation is confirmed. Along a first direction perpendicular to the elongation direction and from a position X1 set in the tungsten carbide particle toward a position X2 set in the binding phase adjacent to the tungsten carbide particle, a line analysis is performed using an energy dispersive X-ray spectrometer (TEM-EDX) attached to a transmission electron microscope to measure the distribution of tungsten, cobalt, vanadium and chromium. Here, the direction perpendicular to the elongation direction of the interface refers to the direction of a straight line intersecting at an angle of 90°±5° along the tangent to the elongation direction. The conditions for implementing EDX are an acceleration voltage of 200kV, a camera length of 10cm, a number of pixels of 128×128pixel, and a dwell time of 0.02 to 3s / pixel.
[0101] The measurement results of each of tungsten, cobalt, vanadium, and chromium are shown in a coordinate system in which the X-axis represents the distance from the position X1 and the Y-axis represents the intensity, thereby obtaining a first graph.
[0102] In the cemented carbide, five first images of non-overlapping fields are randomly obtained, and the above analysis is performed based on each first image to obtain five first curve graphs. W <P W70 <P V <P Cr <P Co70 <P Co In the case of the relationship between the hard alloy and the hard alloy, it is judged that the first region of the first curve diagram shows that P W <P W70 <P V <P Cr <P Co70 <P Co In order to obtain this judgment criterion, the inventors of the present invention conducted multiple line analyses on multiple cemented carbides. As a result, it was confirmed that in the first curve graph of more than 80% of these cemented carbides, P W <P W70 <P V <P Cr <P Co70 <P Co It is inferred that the existence forms of vanadium and chromium in the interface region between the WC particles and the binder phase are substantially the same in the same cemented carbide, taking into account the method for producing the cemented carbide.
[0103] P W <P W70<P V <P Cr <P Co70 <P Co The relationship between the WC particles in the cemented carbide, the maximum vanadium concentration area, the maximum chromium concentration area and the positional relationship of the bonding phase can also be confirmed in the HAADF (high-angle annular dark field) image of the cross section of the cemented carbide. Figure 3 is with Figure 2 The graph shows the HAADF image of the same area of the cemented carbide. Figure 3 In the HAADF image shown, the greater the atomic concentration, the higher the brightness.
[0104] Figure 3 The image shown in FIG. 1 is a HAADF image showing the distribution of tungsten atoms. Figure 3 In the image shown in FIG. 1 , the area with the highest brightness corresponds to the area of the WC particles.
[0105] Figure 3 The image shown in Cr is a HAADF image showing the distribution of chromium atoms. Figure 3 In the image shown in Cr, the area with the highest brightness corresponds to the area with the maximum chromium concentration.
[0106] Figure 3 The image shown in V is a HAADF image showing the distribution of vanadium atoms. Figure 3 In the image shown in V, the area with the highest brightness corresponds to the area with the maximum vanadium concentration.
[0107] Figure 3 The image shown in FIG. 1 is a HAADF image showing the distribution of cobalt atoms. Figure 3 In the image shown in Co, the area with the highest brightness corresponds to the area of the bonding phase.
[0108] Depend on Figure 3 The images of W, Cr, V, and C show that, in the first region including the interface between the WC particles and the bonding phase, the maximum vanadium concentration region is located closer to the WC particles than the maximum chromium concentration region, and the maximum chromium concentration region is located closer to the bonding phase than the maximum vanadium concentration region.
[0109] Depend on Figure 3 The W and V images show that the maximum vanadium concentration area is located outside the tungsten carbide particles, not inside the tungsten carbide particles. Figure 3 The images of Cr and Co show that the maximum chromium concentration area is located outside the bonding phase, not inside the bonding phase. Figure 3In the cemented carbide shown, the maximum concentration region of vanadium and the maximum concentration region of chromium exist in the interface region between the WC particles and the binder phase.
[0110] In the first region of the first curve of the cemented carbide of Embodiment 1, the maximum strength I of vanadium is located V The distance P V The vanadium atoms and the maximum intensity I located in the chromium Cr The distance P Cr Chromium atoms can also be present in the W site of tungsten carbide. Figure 4 , and explain the confirmation method.
[0111] Figure 4 is with Figure 2 The same graph as the first graph shown in FIG. 1 is a graph in which the peak of tungsten exists periodically along the X-axis in at least a portion of the first graph. Based on the portion where the period can be clearly confirmed, the average period of the peak of tungsten is calculated. Based on the average period, the peak position P3 of tungsten is recorded in the first graph. In the present disclosure, the peak position P3 is equivalent to the position of the W site. In the present disclosure, there is a C site between adjacent peak positions P3.
[0112] In the first graph, the maximum intensity I of vanadium is determined V The distance P V And the maximum strength of chromium I Cr The distance P Cr In the first graph, the peak position P3 of tungsten and the maximum intensity I V The distance P V In case of overlap, confirm that the V The vanadium atoms are present in the W site of tungsten carbide. In the first graph, the peak position P3 of tungsten and the maximum intensity I of chromium Cr The distance P Cr In case of overlap, confirm that the Cr The chromium atoms are present at the W site of tungsten carbide.
[0113] In the first region of the first curve of the cemented carbide of Embodiment 1, the maximum strength I of vanadium is located V The distance P V The vanadium atoms and the maximum intensity I located in the chromium Cr The distance P Cr The chromium atoms can also exist in the W site of tungsten carbide, but not in the C site.
[0114] <Method for manufacturing cemented carbide>
[0115] The cemented carbide of the present embodiment can be produced by sequentially performing a raw material powder preparation step, a mixing step, a molding step, a sintering step, and a HIP (Hot Isostatic Pressing) step. Each step will be described below.
[0116] <Preparation process>
[0117] The preparation process is a process for preparing raw material powders of materials constituting cemented carbide raw materials. As raw material powders, tungsten carbide powder (hereinafter, also referred to as "WC powder"), cobalt (Co) powder, vanadium carbide (VC) powder, and chromium carbide (Cr3C2) powder can be listed. On the basis of these raw material powders, nickel (Ni) powder, tungsten carbide (TaC) powder, titanium carbonitride (TiCN) powder, etc. can also be prepared. These raw material powders can use commercial products. The average particle size of these raw material powders is not particularly limited, for example, it can be set to 0.1 to 3.0 μm. The average particle size of the raw material powder refers to the average particle size measured by the FSSS method (Fisher Sub-SieveSizer: Fisher particle size measurement method). The average particle size is measured using the "Sub-Sieve Sizer Model 95" (trademark) manufactured by Fisher Scientific.
[0118] <Mixing process>
[0119] The mixing step is a step of mixing the raw material powders prepared in the preparation step at a predetermined ratio. Through the mixing step, a mixed powder is obtained by mixing the raw material powders. The mixing ratio of the raw material powders is appropriately adjusted according to the composition of the target cemented carbide.
[0120] The raw material powders can be mixed using a conventionally known mixing method such as an attritor, a ball mill, or a bead mill. Conventionally known mixing conditions can also be used. The mixing time can be set to, for example, 2 hours to 20 hours.
[0121] After the mixing step, the mixed powder can be granulated as needed. Granulating the mixed powder makes it easy to fill the mixed powder into a die or mold during the molding step described later. Granulation can be performed using a known granulation method, for example, a commercially available granulator such as a spray dryer can be used.
[0122] <Forming process>
[0123] The molding step is a step of molding the mixed powder obtained in the mixing step into a shape for a cutting tool (eg, a round rod shape) to obtain a molded body. The molding method and molding conditions in the molding step may be general methods and conditions, and are not particularly limited.
[0124] <Sintering process>
[0125] The sintering process is a process of sintering the green compact obtained in the forming process and then cooling it to obtain a cemented carbide intermediate. The sintering conditions in this embodiment are as follows. First, the green compact is placed in an argon (Ar) atmosphere at a pressure of 2 kPa, and the green compact is heated to 900 °C and held at 900 °C for 60 minutes (hereinafter, also referred to as "the first sintering"). Then, in an argon (Ar) atmosphere at a pressure of 2 kPa, the green compact is heated to 1100 °C and held at 1100 °C for 60 minutes (hereinafter, also referred to as "the second sintering"). Then, in a vacuum, the green compact is heated to 1350 °C and held at 1350 °C for 60 minutes (hereinafter, also referred to as "the third sintering"). Then, the green compact is cooled. For example, the green compact is cooled to 25 °C in Ar gas under the condition of a pressure of 100 to 400 MPaG. Thus, a cemented carbide intermediate is obtained.
[0126] <HIP process>
[0127] The HIP process is a process of performing HIP treatment on the cemented carbide intermediate. The HIP conditions in this embodiment are as follows. First, a temperature of 1250 °C and a pressure of 10 MPa are applied to the cemented carbide intermediate and held for 30 minutes (hereinafter, also referred to as "the first HIP"). Then, a temperature of 1350 °C and a pressure of 200 MPa are applied to the cemented carbide intermediate and held for 30 minutes (hereinafter, also referred to as "the second HIP"). Thus, the cemented carbide of Embodiment 1 can be obtained.
[0128] <Features of the manufacturing method of the cemented carbide of this embodiment>
[0129] In this embodiment, the sintering process is carried out in three stages including the first sintering, the second sintering, and the third sintering. Further, the HIP process is carried out in two stages including the first HIP and the second HIP. It is speculated that through these processes, the obtained cemented carbide shows a relationship of P in the first region of its first curve graph. W <P W70 <P V <P Cr <P Co70 <P Co As a result of in-depth research by the inventors of the present invention, it was newly found that through such sintering conditions and HIP conditions, the cemented carbide of the present disclosure can be realized. In addition, the sintering conditions and HIP conditions used in this embodiment have not been adopted by those skilled in the art because of the reduction in production efficiency.
[0130] In the conventional manufacturing method of cemented carbide, the sintering process is performed in a stage of heating to a predetermined temperature and then maintaining the temperature for a predetermined time. In addition, in the conventional manufacturing method of cemented carbide, after the sintering process, the HIP process is not performed, or even if it is performed, the HIP process is performed in a stage of maintaining the temperature and pressure for a predetermined time. In the cemented carbide obtained by the conventional manufacturing method of cemented carbide, vanadium and chromium are randomly arranged in the interface region between the WC particles and the binder phase, and P is not shown in the first region of the first curve. W <P W70 <P V <P Cr <P Co70 <P Co relationship.
[0131] [Embodiment 2: Cutting Tool]
[0132] The cutting tool of this embodiment includes a blade tip made of cemented carbide of embodiment 1. In the present disclosure, the blade tip refers to a portion involved in cutting. More specifically, the blade tip refers to an area surrounded by a blade tip ridgeline and an imaginary surface with a distance of 0.5 mm or 2 mm from the blade tip ridgeline to the cemented carbide side.
[0133] Examples of cutting tools include cutting tools, drills, end mills, indexable cutting inserts for milling, indexable cutting inserts for turning, metalworking saws, gear cutting tools, reamers, taps, and the like. In particular, Figure 5 As shown, the cutting tool 10 of the present embodiment can exert excellent effects in the case of a small-diameter drill for processing a printed circuit board. Figure 3 The cutting edge 11 of the cutting tool 10 shown is made of the cemented carbide of the first embodiment.
[0134] The cemented carbide of this embodiment may constitute the whole of these tools or a part thereof. Here, "constituting a part" means a method of forming a cutting edge portion by brazing the cemented carbide of this embodiment to a predetermined position of any base material.
[0135] The cutting tool of the present embodiment may further include a hard film covering at least a portion of the surface of the substrate made of cemented carbide. As the hard film, for example, diamond-like carbon or diamond may be used.
[0136] The cemented carbide of the first embodiment can be formed into a desired shape to obtain the cutting tool of the present embodiment.
[0137] Example
[0138] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.
[0139] [Production of cemented carbide]
[0140] Cemented carbide of each sample was produced according to the following procedure.
[0141] WC powder (average particle size 0.3 μm), Co powder (average particle size 1.0 μm), VC powder, Cr3C2 powder, TaC powder, and TiCN powder were prepared in the proportions described in the "raw material powder" column of Table 1 and Table 2, and mixed using a mill to obtain a mixed powder. The mixing conditions were set to a rotation speed of 300 rpm and 180 minutes. The average particle size of the VC powder, Cr3C2 powder, TaC powder, and TiCN powder was 0.1 to 3.0 μm.
[0142] Table 1
[0143]
[0144] Table 2
[0145]
[0146] Next, the mixed powder is press-formed to produce a round rod-shaped compact. Next, the compact is sintered and then cooled to obtain a cemented carbide intermediate.
[0147] The sintering conditions of samples 1 to 18 are as follows. First, the formed body is placed in an argon (Ar) atmosphere with a pressure of 2 kPa, the formed body is heated to 900°C, and maintained at 900°C for 60 minutes (first sintering). Next, in an argon (Ar) atmosphere with a pressure of 2 kPa, the formed body is heated to 1100°C, and maintained at 1100°C for 60 minutes (second sintering). Next, under vacuum, the formed body is heated to 1350°C, and maintained at 1350°C for 60 minutes (third sintering). Next, the formed body is cooled to 25°C in Ar gas at a pressure of 200 MPaG. Thus, a cemented carbide intermediate is obtained.
[0148] The sintering conditions of Samples 101 to 121 are as follows: The formed body was heated to 1350° C. in vacuum and maintained at 1350° C. for 60 minutes. Next, the cemented carbide intermediate was cooled to 25° C. in Ar gas at a pressure of 400 kPaG. Thus, a cemented carbide intermediate was obtained.
[0149] Next, the cemented carbide intermediate was subjected to HIP treatment to obtain cemented carbide of each sample.
[0150] The HIP conditions of samples 1 to 18 are as follows. First, the cemented carbide intermediate is subjected to a temperature of 1250°C and a pressure of 10 MPa for 30 minutes (first HIP). Next, the cemented carbide intermediate is subjected to a temperature of 1350°C and a pressure of 200 MPa for 30 minutes (second HIP). Thus, the cemented carbides of samples 1 to 18 are obtained.
[0151] The HIP conditions of Samples 101 to 121 are as follows: The cemented carbide intermediate body was subjected to a temperature of 1300° C. and a pressure of 10 MPa for 60 minutes. Thus, the cemented carbides of Samples 101 to 121 were obtained.
[0152] [Manufacturing of cutting tools]
[0153] The obtained carbide round bar is processed to produce a blade diameter Drill bits for printed circuit board processing (PCB (Printed Circuit Board) drill bits).
[0154] [Evaluation of cemented carbide]
[0155] <Content Rate (Volume %) of Tungsten Carbide Particles and Content Rate (Volume %) of Binder Phase in Cemented Carbide>
[0156] The content rate (volume %) of tungsten carbide particles and the content rate (volume %) of binding phase in cemented carbide of each sample are measured. The specific measurement method is as described in Implementation Method 1. The results are shown in the "WC particle content rate" and "binding phase content rate" columns of "cemented carbide" in Table 3 and Table 4. Furthermore, the total content rate of tungsten carbide particles and the content rate of binding phase in cemented carbide is shown in the "WC particle + binding phase content rate" column of "cemented carbide" in Table 3 and Table 4. In Table 3 and Table 4, it is confirmed that the cemented carbide with a "WC particle + binding phase content rate" column lower than 100% by volume contains TiCN, TiC, etc.
[0157] <Cobalt Content in Binder Phase>
[0158] In the cemented carbide of each sample, the cobalt content in the binder phase was measured. The specific measurement method is as described in Implementation Example 1. The results are shown in the "Co content in binder phase" column of "Cemented carbide" in Table 3 and Table 4. In Table 3 and Table 4, it is confirmed that the binder phase with a "Co content in binder phase" column of less than 100% by mass contains inevitable impurities such as Ni.
[0159] <Vanadium Content and Chromium Content in Cemented Carbide>
[0160] The vanadium content and chromium content of the cemented carbide of each sample were measured. The specific measurement method is as described in Embodiment 1. The results are shown in the "V content" and "Cr content" columns of "cemented carbide" in Tables 3 and 4.
[0161] <Line Analysis>
[0162] The line analysis shown in Embodiment 1 was performed on the cemented carbide of each sample to obtain a first graph. In the first graph of each sample, it was confirmed that the maximum strength I of tungsten W The distance P W , represents the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 、The maximum strength of vanadium I V The distance P V 、The maximum strength of chromium I Cr The distance P Cr , represents the maximum strength of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 , and maximum intensity I Co The distance P Co Is P shown? W <P W70 <P V <P Cr <P Co70 <P Co The results are shown in the "Peak Order" column of Table 3 and Table 4. "Yes" means that P W <P W70 <P V <P Cr <P Co70 <P Co "No" means not showing P W <P W70 <P V <P Cr <P Co70 <P Co relationship.
[0163] Based on the first curve of each sample, the maximum intensity I at vanadium was confirmed by the method described in Embodiment 1. V The distance P V The vanadium atoms and the maximum intensity I located in the chromium Cr The distance P CrThe results are shown in the "V, Cr Existence Site" column of Table 3 and Table 4. In the "V, Cr Existence Site" column, "W" indicates that the vanadium atom and the chromium atom are present at the W site of tungsten carbide. In the "V, Cr Existence Site" column, "W, C" indicates that the vanadium atom and the chromium atom are present at both the W site and the C site of tungsten carbide.
[0164] Table 3
[0165]
[0166] Table 4
[0167]
[0168] [Evaluation of cutting tools]
[0169] <Cutting test>
[0170] The PCB drill bits of each sample were used to perform hole-drilling processing on commercially available printed circuit boards for semiconductor packaging, and the tool life was evaluated. The printed circuit board is made by overlapping three substrates with a thickness of 0.4 mm. The conditions for the hole-drilling processing were set to a rotation speed of 150 krpm, a feed speed of 3 m / min, and a pulling speed of 25 m / min. Ten PCB drill bits of each sample were prepared, and each drill bit was used to perform hole-drilling processing, and the number of drill bits that were broken until 10,000 hits was counted. The results are shown in the "Number of drill bit breakage" column of the "Cutting test" in Tables 3 and 4. The fewer the number of drill bit breakages, the better the drill bit's breakage resistance and the longer the tool life.
[0171] <Inspection>
[0172] The cemented carbides and cutting tools of samples 1 to 18 correspond to the examples. The cemented carbides and cutting tools of samples 101 to 121 correspond to the comparative examples. It was confirmed that the tool life of the cutting tools of samples 1 to 18 (examples) was longer than that of the cutting tools of samples 101 to 121 (comparative examples). It is presumed that this is because the cemented carbides of samples 1 to 16 have excellent breakage resistance.
[0173] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.
[0174] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.
[0175] Description of Reference Numerals
[0176] 1: tungsten carbide particles; 2: bonding phase; 3: cemented carbide; 10: cutting tool; 11: tool tip.
Claims
1. A cemented carbide comprising a plurality of tungsten carbide particles and a binding phase, wherein: The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 0.1 volume % or more and 20 volume % or less of the binder phase, The cemented carbide contains 0.03 atomic % or more and 0.90 atomic % or less of vanadium, The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium, The binding phase contains 50 mass % or more of cobalt, The results of line analysis along a first direction from a position X1 disposed in the tungsten carbide particle toward a position X2 disposed in the binding phase adjacent to the tungsten carbide particle using an energy dispersive X-ray spectrometer attached to a transmission electron microscope are shown in a first region of a first graph obtained in a coordinate system in which the X-axis is the distance from the position X1 and the Y-axis is the intensity. Maximum Strength of Tungsten I W The distance P W , represents the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 、The maximum strength of vanadium I V The distance P V 、The maximum strength of chromium I Cr The distance P Cr , represents the maximum strength of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 and the maximum intensity I Co The distance P Co Show P W <P W70 <P V <P Cr <P Co70 <P Co relationship, The first region is a region between a distance P1 and a distance P2 in the first curve graph, wherein the distance P1 is a distance from the distance P2 on the X-axis. V The distance from the origin of the coordinate system to the coordinate system is 3 nm, and the distance P2 is 3 nm from the P V The distance to the side opposite to the origin is 3 nm.
2. The cemented carbide according to claim 1, wherein: Located in the P V The vanadium atoms and the Cr The chromium atoms are present at the W site of tungsten carbide.
3. The cemented carbide according to claim 1 or 2, wherein: The cemented carbide contains 18 volume % or less of the binder phase. 4 . A cutting tool comprising a cutting edge made of the cemented carbide according to claim 1 .
Citation Information
Patent Citations
Hard metal alloy
JP2016098393A
Ultrafine particle cemented carbide, and tool for cutting or cutting grinding or tool for wear resistance using the same
JP2021110010A